2020
DOI: 10.1177/2045894020910685
|View full text |Cite
|
Sign up to set email alerts
|

Atrial arrhythmias in chronic lung disease‐associated pulmonary hypertension

Abstract: Atrial arrhythmias are common during episodes of acute respiratory failure in patients with chronic lung disease-associated pulmonary hypertension. Expert opinion suggests that management of atrial arrhythmias in patients with pulmonary hypertension should aim to restore sinus rhythm. This is clinically challenging in pulmonary hypertension patients with coexisting chronic lung disease, as there is controversy on the use of rhythm control agents; generally, in regard to either their pulmonary toxicity profile … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 108 publications
(272 reference statements)
0
8
0
Order By: Relevance
“…Up-to-date studies have shown that anticancer therapies may induce cardiotoxicities, such as corrected QT interval prolongation and arrhythmia [ 101 ]. Additionally, Vahdatpour et al found that atrial arrhythmia can be secondary to chronic lung disease-associated pulmonary hypertension [ 102 ]. Due to its prevalence and accompanying adverse events, investigation about arrhythmia has deepened, and we are now looking at the implications between gut microbiota and arrhythmia.…”
Section: Implications Of Gut Microbiota In Cvdsmentioning
confidence: 99%
“…Up-to-date studies have shown that anticancer therapies may induce cardiotoxicities, such as corrected QT interval prolongation and arrhythmia [ 101 ]. Additionally, Vahdatpour et al found that atrial arrhythmia can be secondary to chronic lung disease-associated pulmonary hypertension [ 102 ]. Due to its prevalence and accompanying adverse events, investigation about arrhythmia has deepened, and we are now looking at the implications between gut microbiota and arrhythmia.…”
Section: Implications Of Gut Microbiota In Cvdsmentioning
confidence: 99%
“…Arrhythmias are related to the severity of COVID-19 disease and could be the result of direct or indirect damage to myocardial tissue caused by multiple mechanisms ( 8 ). Pulmonary damage and its progression determine the prognosis during COVID-19 infection ( 9 ) and inflammation in pulmonary infections has been described as a trigger factor for arrhythmias ( 10 ).…”
Section: Introductionmentioning
confidence: 99%
“… 24 Similarly, the abovementioned gap was reinforced in recent reviews on AF, COPD, and pulmonary hypertension. 25 , 26 …”
Section: Discussionmentioning
confidence: 99%